Pandemic natives: preschoolers remote learning during COVID-19 confinement - Fernandez-Ruiz, Maria (My University, 2021)
The aim of this research is to analyze the development of remote learning in preschool educa- tion during the COVID-19 pandemic. This study de- ploys descriptive and inferential statistics to interpret the data collected from preschoolers (n=267) from seven schools in Malaga. The results offer an over- view of the constraints of virtual education, showing a correlation between routines and children's com- mitment, enjoyment of tasks, activities carried out as a family, how their development has been affected by the lack of face-to-face education, participation in videoconferences, and coordination with teachers. We conclude that the education of these pandemic natives requires greater attention from policy makers, schools and their own families. Keywords:
PUBLISHED
Keywords: Preschool education, COVID-19, Remote learning, Quantitative analysis